Calappa karenae, a new species of box crab from Guam (Crustacea: Decapoda: Brachyura: Calappidae) - Ng, Peter K. L.; Lai, Joelle C. Y. (Zootaxa, 2012)
A new deep-water species of box crab, Calappa karenae sp. nov. (Brachyura: Calappidae) is described from Guam. Thenew species differs from its congeners by its distinctive colouration and conspicuously wide carapace. It is one of the largest Calappa species known from the Indo-West Pacific.